Phenolic compound from hexane extract of root bark of garcinia mangostana / Muhammad Hafizudin Abdullah - Abdullah, Muhammad Hafizudin (Faculty of Applied Sciences, 2017)
Extensive work on the isolating of secondary metabolites from Malaysian flora, root barks Garcinia mangostana was chosen for further phytochemical analysis. This plant was going for detail separation work which involves extraction and isolation of chemical component using a various techniques of analysis. Xanthones was found as a major component from the isolation of this plant. Detail work on the hexane extract of Garcinia mangostana has afforded two known xanthones, a-mangostin and osajaxanthone. These pure compounds were elucidated by using numerous spectroscopic analysis, such as ID and 2D NMR, MS, IR, UV and also by comparison with the previous data.